Blast protection in urban areas using protective plants. Issue 2 (June 2018) - Gebbeken, Norbert; Warnstedt, Paul; Rüdiger, Lars
The increased threats by terroristic actions require the protection of urban areas. The protective potential of currently available protective systems is often recognizable, which may therefore raise the perceived threat. This is acceptable for temporary solutions but in the long-term contrary to the idea of a modern and open society. For permanent use, new solutions, which are not recognized as protective elements and deploy their protective potential inconspicuously, should be considered. Among them, there are elements of city furniture and landscape architecture. This article addresses theoretical, numerical, and experimental research towards protection capabilities of plants against blast. The research shows that plants of certain characteristics reduce the blast pressure by up to 60% compared to unimpeded blast wave propagation. These first studies pose specific questions that need to be answered in further research.